MicroRNA biomarkers in clinical renal disease: from diabetic nephropathy renal transplantation and beyond. (December 2016) - Nassirpour, Rounak; Raj, Dominic; Townsend, Raymond; Argyropoulos, Christos
Abstract: Chronic Kidney Disease (CKD) is a common health problem affecting 1 in 12 Americans. It is associated with elevated risks of mortality, cardiovascular disease, and high costs for the treatment of renal failure with dialysis or transplantation. Advances in CKD care are impeded by the lack of biomarkers for early diagnosis, assessment of the extent of tissue injury, estimation of disease progression, and evaluation of response to therapy. Such biomarkers should improve the performance of existing measures of renal functional impairment (estimated glomerular filtration rate, eGFR) or kidney damage (proteinuria). MicroRNAs (miRNAs) a class of small, non-coding RNAs that act as post-transcriptional repressors are gaining momentum as biomarkers in a number of disease areas. In this review, we examine the potential utility of miRNAs as promising biomarkers for renal disease. We explore the performance of miRNAs as biomarkers in two clinically important forms of CKD, diabetes and the nephropathy developing in kidney transplant recipients. Finally, we highlight the pitfalls and opportunities of miRNAs and provide a broad perspective for the future clinical development of miRNAs as biomarkers in CKD beyond the current gold standards of eGFR and albuminuria.